Evaluation of Plant Tissue Analysis to Assess Phosphorus Nutritional Status for Corn and Soybean - Gustavo A. Roa; Edmond B. Rutter; Dorivar A. Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2023)
Plant tissue samples can be used to assess nutrient concentrations and the response to phosphorus fertilization. This study aimed to identify critical phosphorus tissue concentrations for corn and soybean at different growing stages. The experiment was conducted at 23 locations for corn in 2021–2022 and 12 locations for soybean in 2017–2020 across Kansas. Tissue samples were collected from whole corn plants at the V6 stage, corn ear leaves at the R1 stage, and whole soybean plants at the V4 stage, and upper trifoliate leaves at the R2 soybean stage. Data from plots that received no phosphorus fertilization were used to investigate the relationships between plant tissue P concentration and relative yield. Linear-plateau models were used to determine the critical values: whole corn plants at V6 = 0.41%; corn ear leaves at R1 = 0.27%; whole soybean plants at V4 = 0.34; and trifoliate leaves at R2 = 0.39%. The study found a moderate correlation between the concentration at V6 and R1 for corn (R2= 0.54) and a weak correlation between the concentration of whole plants at V4 and trifoliate at R2 for soybean (R2= 0.40).
Keywords: Phosphorus; tissue analysis; nutritional status; corn; soybean